Modulation of the endocannabinoid system by (S)-ketamine in an animal model of depression - Nicole R. Silva; Shokouh Arjmand; Luana B. Domingos; Adriano M. Chaves-Filho; Melina Mottin; Caroline C. Real; Anna L. Waszkiewicz; Pedro H. Gobira; Alessio Nicola Ferraro; Anne M. Landau; Carolina H. Andrade; Heidi K. Müller; et al. (Pharmacological Research)
Ketamine (KET) is recognized as rapid-acting antidepressant, but its mechanisms of action remain elusive. Considering the role of endocannabinoids (eCB) in stress and depression, we investigated if S-KET antidepressant effects involve the regulation of the eCB system using an established rat model of depression based on selective breeding: the Flinders Sensitive Line (FSL) and their controls, the Flinders Resistant Line (FRL). S-KET (15 mg/kg) effects were assessed in rats exposed to the open field and forced swimming test (FST), followed by analysis of the eCB signaling in the rat prefrontal cortex (PFC), a brain region involved in depression neurobiology. Changes in eCB receptors and enzymes were assessed at mRNA and protein levels (qPCR and western blot), CB1 binding ([3H]SR141716A autoradiography) and endocannabinoid content (lipidomics). The results demonstrated that the depressive behavior in FSL was negatively correlated with 2-AG levels, which were restored upon acute S-KET treatment. Although S-KET decreased CB1 and FAAH gene expression in FSL, there were no significant changes at protein levels. [3H]SR141716A binding to CB1 receptors was increased by S-KET and in silico analysis suggested that it binds to CB1, CB2, GPR55 and FAAH. Overall, S-KET effects correlated with an increased endocannabinoid signaling in the PFC, but systemic treatment with rimonabant failed to block its behavioral effects. Altogether, our results indicate that S-KET facilitates eCB signaling in the PFC of FSL. The inability of rimonabant to block the antidepressant effect of S-KET highlights the complexity of its interaction with the ECS, warranting further investigation into the molecular pathways.